Analisis Disparitas Pencari Kerja dan Lowongan Pekerjaan di Kota Medan Tahun 2023-2024 - Mahara Sintong; Sahala Fransiscus Marbun; Vadillah Raihto Hutasuhut; Sri Andini; Delon Sitompul; Debora Zega; Hayqal Adibya; Angelo Simanullang; Grace Dachi (Jurnal Visi Manajemen, 2026)
This study aims to analyze the disparity between the number of job seekers and available job vacancies in Medan City during 2023–2024, a condition that reflects a significant imbalance in the local labor market. The background of this research arises from the persistent surplus of job seekers, coupled with the sharp decline in job openings that suggests the presence of structural unemployment and a mismatch between educational qualifications and labor market needs. Using a quantitative-descriptive approach through literature review and secondary data analysis from official labor statistics, this study provides a comprehensive overview of the labor market dynamics in Medan City. The findings show that in 2023, there were 4,661 registered job seekers compared to only 2,777 available vacancies, resulting in a surplus of 1,884 individuals. The situation worsened in 2024 as job vacancies dropped drastically to 1,016 positions, while the number of job seekers reached 2,293, leaving a surplus of 1,277 individuals. The study also reveals that job seekers are predominantly senior high school graduates, accounting for approximately 80 percent of the total, while job vacancies are concentrated in the manufacturing and trade sectors—both of which experienced severe contraction in 2024. These conditions reflect multidimensional mismatches in the labor market, including vertical and horizontal mismatches, as well as a structural shift towards a service-based economy that has not fully absorbed the workforce. The implications of this study highlight the urgency of strengthening vocational training programs, aligning educational curricula with industry needs, diversifying the local economy, and enhancing job seekers’ competencies to improve competitiveness in an increasingly challenging labor market.